Programmatic Advertising and the changes in the digital industry - Fuentes Santos, Paloma; Bustos Díaz, Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Programmatic advertising and its technologies, traditional media buying has been replaced by audience segment buying. The criterion is no longer the context but the interests of the users to whom we want to show certain ads, which we know thanks to their browsing profile among other sources. A qualitative research methodology has been used. Along with the above, we have studied cookies, their relevance in the programmatic advertising ecosystem and what the disappearance of third party cookies in Google Chrome would mean.